Association of atrial fibrillation and gastroesophageal reflux disease: Natural and therapeutic linkage of the two common diseases. Issue 1 (12th October 2018) - Maruyama, Toru; Fukata, Mitsuhiro; Akashi, Koichi
Abstract: Atrial fibrillation (AF) is a common arrhythmia and gastroesophageal reflux disease (GERD) is popular in Japan. The two common diseases share several predisposing factors such as lifestyle and senescence, and inflammation and oxidative stress play an important role in their development and progression. Incidental cases of AF treated successfully by proton pump inhibitor (PPI) applied for coexisting GERD have been sporadically reported. An increasing evidence indicates that GERD induces the initiation and the perpetuation of AF. This is caused by the autonomic nerve influence, mechanical compression, and propagation of local inflammation due to proximity of left atrium (LA) and lower esophagus. Meanwhile, AF also develops GERD by mechanical and inflammatory actions of LA characterized by remodeling and inflammation. The robust association of AF with GERD is not limited to their natural interaction, i.e., pharmacological or nonpharmacological treatment of AF is reported to aggravate GERD. Many cardiac drugs (anticoagulants, calcium antagonists, and nitrates) induce esophageal mucosal damage and lower esophageal sphincter relaxation promoting acid reflux. These drugs are frequently prescribed in patients with AF for stroke prevention, rate control, and for coexisting coronary heart disease. Catheter ablation also yields both GERD and esophageal thermal injury, which is a precursor lesion of atrioesophageal fistula. The notion that AF and GERD are mutually interdependent is widely and empirically recognized. However, mechanistic link of the two common diseases and objective evaluation of PPI as an adjunctive AF treatment warrant future large‐scale prospective trials.